Non-fungible tokens - Florian Idelberger; Péter Mezei (Internet Policy Review, 2022)
Blockchain-based NFTs (non-fungible tokens) are uniquely identifiable digital representations of physical or digital items. Usually, the tokens are indivisible into smaller units. NFTs represent structured metadata referring to physical or digital objects. The tokens act as separate identifier and are often not tied to the objects. Their proponents claim they further the interoperable commercialisation of digital or physical goods.
Keywords: 300; Non-fungible tokens; Blockchain; Copyright law